1998
DOI: 10.1007/s11746-998-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyfunctional glycerol esters: Lipase‐Catalyzed esterification of glycerol with diesters

Abstract: The enzymatic esterification of glycerol with dicarboxylic acids or esters was studied to produce mono-and/or diesterified glycerol adducts. Such materials are useful synthons in the synthesis of biodegradable polymers and surfactants. In this work two strategies were studied for preparing these prepolymeric glycerol derivatives: the lipase-catalyzed esterification of free glycerol with diacids or esters and the reaction of supported or protected glycerol with diesters. For example, reaction of isopropylidene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Our research group has explored the direct utilization of refined glycerol to produce mono-and diesterified adducts [1] and hyperbranched polyesters [2,3]. Identifying new uses for glycerol would be of great benefit to the biodiesel industry because glycerol is the principle coproduct made from the transesterification process by which biodiesel is produced.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has explored the direct utilization of refined glycerol to produce mono-and diesterified adducts [1] and hyperbranched polyesters [2,3]. Identifying new uses for glycerol would be of great benefit to the biodiesel industry because glycerol is the principle coproduct made from the transesterification process by which biodiesel is produced.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the importance of the water content of the system was shown (Green and Nakajima, 1998;Haraldsson and Thorarensen, 1999;McNeill and Sonnet, 1995;Rosu et al, 1999;Villeneuve et al, 1998). Some studies reported that the water thermodynamic activity (a w ) is conditioning the lipase spatial structure and thus its enzymatic activity either toward synthesis or hydrolysis (Chandler et al, 1998;Soumanou et al, 1998b;Svensson et al, 1994;Valivety et al, 1992Valivety et al, , 1994Villeneuve et al, 1997a;Lee and Foglia, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge the vacuum conditions reported here were being used for the first time in thioesterification and transthioesterification reactions with lipases. However, other lipase-catalyzed esterifications and transesterifications in vacuo are well known (e.g., [17][18][19].…”
Section: Discussionmentioning
confidence: 99%